Modeling Distribution and Habitat Suitability for the Snow Leopard in Bhutan - Lham, Dechen; Cozzi, Gabriele; Sommer, Stefan; Thinley, Phuntsho; Wangchuk, Namgay; Wangchuk, Sonam; Ozgul, Arpat (Frontiers in Conservation Science, 2021)
The snow leopard (Panthera uncia) is one of the world’s most elusive felids. In Bhutan, which is one of the twelve countries where the species still persists, reliable information on its distribution and habitat suitability is lacking, thus impeding effective conservation planning for the species. To fill this knowledge gap, we created a country-wide species distribution model using ‘presence-only’ data from 420 snow leopard occurrences (345 from a sign survey and 77 from a camera-trapping survey) and twelve environmental covariates consisting of biophysical and anthropogenic factors. We analyzed the data in an ensemble model framework which combines the outputs from several species’ distribution models. To assess the adequacy of Bhutan’s network of protected areas and their potential contribution towards the conservation of the species, we overlaid the output of the ensemble model on the spatial layers of protected areas and biological corridors. The ensemble model identified 7,206 km2 of Bhutan as suitable for the snow leopard: 3,647 km2 as highly suitable, 2,681 km2 as moderately suitable, and 878 km2 as marginally suitable. Forty percent of the total suitable habitat consisted of protected areas and a further 8% of biological corridors. These suitable habitats were characterized by a mean livestock density of 1.34 individuals per hectare, and a mean slope of 25º; they closely match the distribution of the snow leopard’s main wild prey, the bharal (Pseudois nayaur). Our study shows that Bhutan’s northern protected areas are a centre for snow leopard conservation both at the national and regional scale.